2010
DOI: 10.1016/j.compedu.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication technologies in the life of university freshmen: An analysis of change

Abstract: The passage from secondary school to university puts students in an environment with different expectations. Not only the expectations towards learning might change, but also towards ICT competences and computer use. The purpose of this article is to find out whether freshmen, after six months at the university, changed their self-perception of ICT competences and computer use in comparison with their behaviour at secondary school, and what factors can explain the self-perception of ICT competences and compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 47 publications
4
39
0
2
Order By: Relevance
“…Vekiri (2010b) found a relatively positive attitude of students (male and female) toward ICT lessons and a weak but significant positive correlation between class instruction for ICT and the self-efficacy beliefs of boys and girls. Other observations in 2004, 2005(Verhoeven et al, 2010De Wit et al, 2012) have confirmed that university freshers who took ICT classes in secondary school considered themselves more capable of applying some ICT skills, but not all. Therefore, we examine in our model whether having taken ICT courses in secondary school has an influence on the ICT skills of bachelor's students.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Vekiri (2010b) found a relatively positive attitude of students (male and female) toward ICT lessons and a weak but significant positive correlation between class instruction for ICT and the self-efficacy beliefs of boys and girls. Other observations in 2004, 2005(Verhoeven et al, 2010De Wit et al, 2012) have confirmed that university freshers who took ICT classes in secondary school considered themselves more capable of applying some ICT skills, but not all. Therefore, we examine in our model whether having taken ICT courses in secondary school has an influence on the ICT skills of bachelor's students.…”
Section: Introductionmentioning
confidence: 62%
“…Many publications have shown that girls and women are less keen to work with a computer or to apply ICT programs or ICT instruments compared with boys and men (Volman & van Eck, 2001;Losh, 2004;Becker, 2006;Madigan et al, 2007;Kubiatko, 2010;Zhao et al, 2010;van Deursen & van Dijk, 2015). However, research (Bovée, Voogt, & Meelissen, 2007;Wang, Wu, & Wang, 2009;Verhoeven et al, 2010;De Wit et al, 2012) has also demonstrated that the gap between male and female actors is not common to all types of use of ICT applications and not in all countries (Spiezia, 2010), and that women (researchers) are more proficient in some ICT skills than men are (Chowdhury et al, 2011). With regard to the link between gender and ICT and research in secondary education, Hohlfeld, Ritzhaupt, and Barron (2013) even concluded "that the gender gap for demonstrated technology skills has closed", although this observation was not confirmed by the longitudinal study among adults by van Deursen and van Dijk (2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in former articles (De Wit et al, in press;Verhoeven et al, 2010) we have already shown that first year students in the humanities are less competent than students in biomedical and other sciences with regard to using a spreadsheet to make graphs or perform calculations and with regard to using computers and the Internet for emailing. If ICT is important for educational attainment and if knowledge of ICT competences differs between different groups of students, then it makes sense to hypothesize that ICT competences may have differing influences on the achievements of students.…”
Section: Editor: Meliha Handzicmentioning
confidence: 99%
“…Moreover, most major universities use a VLE (virtual learning environment, e.g., Blackboard) to support teaching and study. Research has shown that there is a wide range of ICT capabilities among university students (De Wit, Heerwegh & Verhoeven, in press;Lee, 2003;Palaigeorgiou, Siozos, Konstantakis, & Tsoukalas, 2005;Pillay, Irving, & Tones, 2007;Verhoeven, Heerwegh, & De Wit, 2010).…”
Section: Editor: Meliha Handzicmentioning
confidence: 99%